Pengukuran Kepuasan Pengguna Layanan Pajak E-Filing Menggunakan IPA (Importance Performance Analysis) Studi Kasus Di Universitas Pendidikan Indonesia - Visma Dewi Damayanti; Arry Irawan (Indonesian Accounting Literacy Journal, 2021)
Tax is one of the sources of state revenue. Every citizen who has an income of up to 60 million and above is obliged to report taxes to the Directorate General of Taxes. Tax reporting by taxpayers is currently done online through e-filing. Every taxpayer in their online tax reporting has the ability to use the internet, but in practice the tax reporting experiences several obstacles. For this tax reporting, it is expected that taxpayers have convenience in tax reporting, so that taxpayers feel satisfied. The satisfaction of this service needs to be investigated specifically. This research was conducted on employees and lecturers at the University of Education Indonesia. The purpose of this study is to determine the expectations and performance of tax services by the Directorate General of Taxes. The research method uses descriptive data analysis with IPA (Importance Performance Analysis)